Evaluating the Clinical Outcomes of Total Hip Arthroplasty Utilizing Dual Mobility Implants: A Comprehensive Review - Sajjad Hussain Bhatti; Niaz Hussain Keerio; Abdul Samad Qureshi; Muhammad Azfar Khanzada; Asfandyar Khan; Nadeem Hassan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective This study set out to evaluate the clinical results of total hip arthroplasty (THA) with a dual mobility implant (DMI). Study design: A prospective cohort study Place and Duration: This study was done at, Pir Abdul Qadir Shah Jillani Institute of Medical Sciences GIMS Gambat Khairpur mir’s for period of one years from March 2024 to March 2025. Methodology Total 30 patients participated for this study. The patients were both male and female. The age bracket was from 32 years to 75 years. There were several reasons for which these patients were on the list of THA. Patients were assessed clinically and a radiograph of each patient was taken before the surgery. A DMI was used in the surgery. Patients were asked to attend their follow-up visit after three months of the surgery. This visit was arranged to check if there is any sign of dislocation. Results The ratio of male patients to female patients was 1.5:1. There were 18 (60%) male patients and 12 (40%) female patients. The average age of the patients was 60.21 ± 9.25 years. Harris Hip Score (HHS) of the patients was recorded before the surgery and an average of HHS was 47.70 ± 6.85. It improved after the surgery and was seen to be 85.25 ± 7.29 (p < 0.001). No patient was diagnosed with dislocation on the three months follow up visit. Conclusion The results of the study demonstrate that there was a significant improvement in the HHS of the patients treated by THA using a DMI and there was no dislocations observed after the surgery.